Design and Implementation of the Algorithm on Automatically Generating Vouchers in Financial Software - Bai, Dong; Han, Jia Wu (Applied Mechanics and Materials, 2014)
Automatic generation algorithm vouchers, the use of the algorithm can depart from any data source, in any condition defined abstract formulas, subjects formula, the amount of formula and other formulas, then by definition generates vouchers, thereby reducing the workload of finance staff to improve accounting accounting standards.